Decomposition of rice straw residues and the emission of CO2, CH4 under paddy rice and crop rotation in the Vietnamese Mekong Delta region - A microcosm study - Tran Van Dung; Tat Anh Thu; Vu Van Long; Chau Thi Da (Plant, Soil and Environment, 2022)
This study investigated the influence of soil undergoing different crop rotations on the CH4, CO2 emissions, and decomposition of rice straw. The studied soil undergoing crop rotation systems were rice-rice-rice (SR) and baby corn-rice-mungbean (SB). Two main microcosm set-ups: anaerobic (SR-AN, SB-AN) and aerobic (SR-AE, SB-AE) conditions. Litter bags containing rice stems were inserted into the soil and recollected at different time points for chemical analysing and the gas sampling was collected to measure the CO2 and CH4 emissions. The results indicated that the total carbon (TC) decreased around 30%, and the TC removal in anaerobic was significantly higher than in aerobic conditions. The residue cellulose content varied in a range from 68.2% to 78.6%, while the hemicellulose content varied from 57.4% to 69.3% at day 50 after incorporation. There were no significant differences in the total nitrogen removal, cellulose, hemicellulose, and lignin contents among the microcosm set-ups. CO2 emission increased in all the microcosm set-ups with the treatments without rice straw (CTSR, CTSB) in both aerobic and anaerobic conditions. CH4 release in the SR-AN treatments did not differ significantly compared with the SB-AN treatments. This study confirmed that the decomposition of rice straw residues is faster in the anaerobic paddy soil condition compared to the aerobic crop rotation condition.